The Ethical and Political Contours of Institutional Promotion in Esports : From Precariat Models to Sustainable Practices - Florence Chee; Veli-Matti Karhulahti (Finland, 2025)
This study evaluated five early cases in which esport developer Riot Games made rulings regarding activities and infractions by members of various institutions related to its product, League of Legends. The findings of this study support future theoretical exploration of other esports in seeking a fuller understanding of issues related to consent, power differentials, and roles and behaviors expected of the institutional activities of players and teams in competition. Increased investigation of these—and other—issues from an ethical standpoint could lead to a framework that not only would facilitate future study but also bring opportunities for improvements in practices in concert with necessary policy changes.